Science and Physics for Saudi Girls: Their Perceptions, Motivations and Career Perspectives - AlGhamdi, Reem Ahmed R. (Curtin University, 2017)
Using a mixed-method design involving 800 students in Years 9, 10, and 11, this research examined how Saudi girls’ perceptions, motivations, and career perspectives influenced their attraction towards the study of science and physics. Saudi girls enjoy science disciplines that have personal relevance and align with their stereotypic views. Biology topics, especially those related to medicine, engender more motivation than physics topics. Nevertheless, Saudi girls receive support from family to study any chosen science discipline.